Роковая ночь: [роман] / Юлия Шилова - Шилова Юлия Витальевна (Час криминала, 2001)
Экземпляры: ф. 9 (20220719) / Инвентарный номер: 63860 / Цена: 20.00 / Авт.знак: Ш 59 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6